Present day medical education in India: Is it serving the purpose? - Dhaniwala, N. S. (Journal of Medicine and Health Sciences Research, 2019)
Medical Education in India is passing through multiple modifications. It is considered failing in producing well trained doctors to cater to our health needs. Doctors on the other hand, are facing problems from society, medical schools and due to consumer protection act. The etiology of this situation is multifactorial and requires serious consideration to improvement.